2019
DOI: 10.3390/jcm8111978
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Osteochondral Scaffold for the Treatment of Focal Articular Cartilage Defects in Early Knee OA: 5 Years’ Follow-Up Results

Abstract: The purpose of this study was to investigate the clinical results at five years’ follow-up of a tri-layered nanostructured biomimetic osteochondral scaffold used for focal articular cartilage defects in patients meeting the criteria of early osteoarthritis (EOA). The study population comprised 22 patients (mean age: 39 years), prospectively assessed before surgery, at 24 and 60 months’ follow-up. Inclusion criteria were: at least two episodes of knee pain for more than 10 days in the last year, Kellgren-Lawren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
(47 reference statements)
0
18
0
Order By: Relevance
“…Earlier literature findings support the rationale of using the osteochondral approach, which partially overcomes some limitations of chondral regenerative options, such as ACI/MACT. 3,12,33 Different authors combined ACI/ MACT with bone grafting to treat knee osteochondritis dissecans, showing benefits enduring up to long-term followup. 1 However, Roffi et al 31 showed poorer results for larger lesions, 31 and Berruto et al 5 observed that patients with osteochondritis dissecans had better outcomes compared with patients with posttraumatic or degenerative etiology in their series on a mixed population at a long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier literature findings support the rationale of using the osteochondral approach, which partially overcomes some limitations of chondral regenerative options, such as ACI/MACT. 3,12,33 Different authors combined ACI/ MACT with bone grafting to treat knee osteochondritis dissecans, showing benefits enduring up to long-term followup. 1 However, Roffi et al 31 showed poorer results for larger lesions, 31 and Berruto et al 5 observed that patients with osteochondritis dissecans had better outcomes compared with patients with posttraumatic or degenerative etiology in their series on a mixed population at a long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…5 In this regard, previous studies reported superior outcomes in cases of complex defects and satisfactory shortand midterm results as a salvage procedure even in osteoarthritis of the knee settings, where chondral regeneration showed a lower potential. 3,12,33 Moreover, a randomized controlled trial 18 recently underlined the scaffold superiority versus microfractures for patients affected by deep osteochondral lesions (ie, Outerbridge grade IV and osteochondritis dissecans), also in the challenging group of sports-active patients. In this heterogeneous series of patients, all questionnaires confirmed significant benefits at the long-term follow-up, both for isolated lesions of the articular surface and for more complex knee defects, requiring multiple procedures to restore the appropriate biomechanical environment and facilitate the osteochondral regeneration process performed by the scaffold implantation.…”
Section: Discussionmentioning
confidence: 99%
“…The results presented are particularly relevant for a number of reasons: first, because of the paucity of data on osteochondral scaffolds, and second, because this is the only multicenter trial available on the use of an osteochondral scaffold in OA knees with the highest number of patients included to date (N = 86). Another major point is that, as opposed to other reports, 7,42 only a small number of patients in the present series (n = 19) underwent concurrent surgery (only 2 were major procedures, ie, high tibial osteotomy), thus allowing a better assessment of the performance of the scaffold itself without the bias of confounding factors. Furthermore, positive outcomes were reported in the most challenging category of patients, those with Kellgren-Lawrence grade 3 OA, for whom there are minimal data in the published literature.…”
Section: Discussionmentioning
confidence: 67%
“…The other scaffold available was introduced more than 10 years ago and is a 3-layered implant consisting of a blend of hydroxyapatite and collagen type I at different percentages within the various layers. 7 Essentially, 2 trials 7,42 investigated the use of this scaffold in patients with early OA. Condello et al 7 documented a success rate of only 69% in a cohort of 26 patients evaluated up to 3 years, whereas Sessa et al 42 evaluated 22 patients and reported satisfactory results up to 5 years with a cumulative failure rate of 16.6%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation